The Phenomenon of Polyphony in the Short Story Collection “The Seagull Man” by the Libyan Writer Hussein Nassib Al-Maliki - Haruna, Haruna Abubakar; Asmai, Ali Mahmood (Al-Uslub: Journal of Arabic Linguistic and Literature, 2022)
This study aims to illuminate the features of the relationship of the narrator character in the story group, with the narrative that contributes to its presentation through the story, and the impact of that relationship on the narrative consistency in it. The Libyan "Hussein Nassib Al-Maliki", who tried through the "polyphony" technique, as he was able, over the course of an extended experience, to dedicate his own narrative voice, And to pass images of condemnation of behaviors and social phenomena that are still destructive in the human spirit, and in the structure of society alike, and it is the most common and expressive of the unity of narrative voice and action in this group of stories. and let her introduce herself, This technique is called polyphony, that spacious world that is based on the idea of pluralism in the narrative components, to give the narrator the blessing of choices and open up to him the vast fields of formulation, and “polyphonic” is achieved in more than one form of narration” the story, the novel, the biography, even the thoughts. This group rose on successive narratives that presented separate perspectives that are united by one spatial space, and are subject to variables that reveal a set of visions of different levels of authority, religious, cultural and sexuality